Characteristics of facies and depositional environment of Tu Chinh - Vung May basin by the results of seismic data analysis - Le Duc Cong; Mai Thanh Tan; Nguyen Trong Tin; Van Thi Thom (Petrovietnam Journal, 2015)
Tu Chinh - Vung May is a sedimentary basin characterised by complex geology and tectonic and volcanic pro-cesses aff ecting sedimentation. Through the analysis and interpretation of seismic stratigraphy based on sequence stratigraphy, the results of the study conducted by the authors allow distribution diagrams, characteristics of facies and depositional environment of Oligocene, lower Miocene, middle Miocene and upper Miocene periods to be con-structed and matched with the results of A well’s geological materials. The results of this study are the premise for further studies to assess the oil and gas potential of Tu Chinh - Vung May basin.